Competitive glucose metabolism as a target to boost bladder cancer immunotherapy - Afonso, Julieta; Santos, Lucio L.; Longatto-Filho, Adhemar [UNESP]; Baltazar, Fatima (Nature Publishing Group, 2020)
Bladder cancer - the tenth most frequent cancer worldwide - has a heterogeneous natural history and clinical behaviour. The predominant histological subtype, urothelial bladder carcinoma, is characterized by high recurrence rates, progression and both primary and acquired resistance to platinum-based therapy, which impose a considerable economic burden on health-care systems and have substantial effects on the quality of life and the overall outcomes of patients with bladder cancer. The incidence of urothelial tumours is increasing owing to population growth and ageing, so novel therapeutic options are vital. Based on work by The Cancer Genome Atlas project, which has identified targetable vulnerabilities in bladder cancer, immune checkpoint inhibitors (ICIs) have arisen as an effective alternative for managing advanced disease. However, although ICIs have shown durable responses in a subset of patients with bladder cancer, the overall response rate is only similar to 15-25%, which increases the demand for biomarkers of response and therapeutic strategies that can overcome resistance to ICIs. In ICI non-responders, cancer cells use effective mechanisms to evade immune cell antitumour activity; the overlapping Warburg effect machinery of cancer and immune cells is a putative determinant of the immunosuppressive phenotype in bladder cancer. This energetic interplay between tumour and immune cells leads to metabolic competition in the tumour ecosystem, limiting nutrient availability and leading to microenvironmental acidosis, which hinders immune cell function. Thus, molecular hallmarks of cancer cell metabolism are potential therapeutic targets, not only to eliminate malignant cells but also to boost the efficacy of immunotherapy. In this sense, integrating the targeting of tumour metabolism into immunotherapy design seems a rational approach to improve the therapeutic efficacy of ICIs.